Kedudukan Dan Fungsi Wakil Presiden Republik Indonesia Dalam Sistem Ketatanegaraan Indonesia - Suparto, Suparto (Fakultas Hukum Universitas Bangka Belitung, 2021)
The position of the Vice President and the President is not equal, even though the President and Vice President are a single inseparable institution. The position of the President and Vice President which is not equal shows that the presidential institution is the organizer of a single government system. The position of the Vice President cannot be separated from the President as a unit of positions which are directly elected by the people through general elections. Then, the duties and powers of the Vice President in the 1945 Constitution do not provide regulation, because the provisions of Article 4 paragraph (2) of the 1945 Constitution only mention their duties as assistant to the President, even though the President and Vice President are a single unit of office elected by the people through general elections. The authority of the Vice President is the authority mandated by the President to assist the President in implementing laws so that the responsibility remains with the President. The authority of the Vice President as a substitute for the President is all the powers that are in the position of President. In the future, it is necessary to make a law as an elaboration of the provisions of Article 4 paragraph (2) of the 1945 Constitution